Over time relationship between platelet reactivity, myocardial injury and mortality in patients with SARS-CoV-2-associated respiratory failure. (19th May 2021) - Campo, Gianluca; Contoli, Marco; Fogagnolo, Alberto; Vieceli Dalla Sega, Francesco; Zucchetti, Ottavio; Ronzoni, Luca; Verri, Marco; Fortini, Francesca; Pavasini, Rita; Morandi, Luca; Biscaglia, Simone; Di Ienno, Luca; et al.
Abstract: The aim of this study (NCT04343053) is to investigate the relationship between platelet activation, myocardial injury, and mortality in patients affected by Coronavirus disease 2019 (COVID-19). Fifty-four patients with respiratory failure due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection were enrolled as cases. Eleven patients with the same clinical presentation, but negative for SARS-CoV-2 infection, were included as controls. Blood samples were collected at three different time points (inclusion [T1], after 7 ± 2 days [T2] and 14 ± 2 days [T3]). Platelet aggregation by light transmittance aggregometry and the circulating levels of soluble CD40 ligand (sCD40L) and P -selectin were measured. Platelet biomarkers did not differ between cases and controls, except for sCD40L which was higher in COVID-19 patients ( p = .003). In COVID-19 patients, P -selectin and sCD40L levels decreased from T1 to T3 and were higher in cases requiring admission to intensive care unit ( p = .004 and p = .008, respectively). Patients with myocardial injury (37%), as well as those who died (30%), had higher values of all biomarkers of platelet activation ( p < .05 for all). Myocardial injury was an independent predictor of mortality. In COVID-19 patients admitted to hospital for respiratory failure, heightened platelet activation is associated with severity of illness, myocardial injury, and mortality. ClinicalTrials.gov number: NCT04343053.